If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+1)=4(x+6)
We move all terms to the left:
3(x+1)-(4(x+6))=0
We multiply parentheses
3x-(4(x+6))+3=0
We calculate terms in parentheses: -(4(x+6)), so:We get rid of parentheses
4(x+6)
We multiply parentheses
4x+24
Back to the equation:
-(4x+24)
3x-4x-24+3=0
We add all the numbers together, and all the variables
-1x-21=0
We move all terms containing x to the left, all other terms to the right
-x=21
x=21/-1
x=-21
| 2(2u-5)=u+2 | | 40+60x=460 | | 2(3x+1)=5(2x+3) | | 11x+14=2x+158 | | 96=4(b+6) | | 26x-125=x | | 7c-2=4c+13 | | 3j-22=-4-3j | | 4(m+4)^2−4m^2+20=276 | | -p+3p=-7+p | | -3x+17=-(17+3x) | | -6y=-4y-18 | | 6(b-10)=8(6+8) | | 4x+7=75-8 | | 2^(x)=32000 | | 3(1-4p)=30-3p | | 8n-6=250 | | 5(3m-8)=38+2m | | 8p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p | | 28=-5(u+1)-2 | | -5v-9(v+6)=-96 | | 21-2w=13 | | 16+6s+9s=16 | | 63=-9a+3(a+3) | | 5(5-2x)=115 | | -8=-v+12/3 | | 3x+3=3x+7 | | 3x+3=-5x-3 | | -70=-4x-3x | | 6(t+1)=84 | | -61=-6(z+7)-13 | | 6x+19=5x-4 |